EFISIENSI PRODUKSI KOMODITAS LADA DI PROPINSI BANGKA BELITUNG - AMIRUDDIN SYAM (SOCA: Jurnal Sosial Ekonomi Pertanian)
Most of Pepper farming in Indonesia is dominantly managed by small holdersplantation that resulted its production currently tends to be low and stagnant. Thiscondition has brought the producing Pepper as an export commodity to a question.Research on the Pepper production efficiency analyses and its factors influence wasconducted to answer the question. The objective of the research is to study thePepper farming performance and its production function included its productionpossibility frontier and which variables might influence the production function. Theresult shows that the Pepper farming is still profitable for the farmers. The TechnicalEfficiency (TE)) average of the sampled farmers is 0.71, means that to increase thePepper production is still prospective. Meanwhile, the distribution of the TE showsthat the Pepper does not have normal distribution. It means that there is still anopportunity to enhance its managerial capability as an internal factor influencing thePepper production (process). In addition to the physical factors such as productioninputs that influence the Pepper production, some other uncontrollable externalfactors i.e. climate and price are also involved in the Pepper production.